2016
DOI: 10.7717/peerj.2254
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between different exercise modes and visuospatial working memory in older adults: a cross-sectional study

Abstract: The purpose of the study was to investigate the relationship between different exercise modes and visuospatial working memory in healthy older adults. A cross-sectional design was adopted. A total of 111 healthy older adults were enrolled in the study. They were classified by the exercise-related questionnaire to be in an open-skill group, closed-skill group or sedentary group. In experiment 1, the participants performed a visuospatial working memory task. The results indicated that both closed-skill (p < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 42 publications
(56 reference statements)
4
44
0
Order By: Relevance
“…Studies that met the following inclusion criteria were considered eligible: (1) full-text studies written in English, (2) studies with an intervention or cross-sectional study design, (3) studies with CSE and OSE specifically defined and discussed as independent variables, and (4) studies that identified at least one cognition-related indicator as a dependent variable. After eliminating duplicate or irrelevant articles, the remaining articles were subjected to a full-text evaluation.…”
Section: Selection Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that met the following inclusion criteria were considered eligible: (1) full-text studies written in English, (2) studies with an intervention or cross-sectional study design, (3) studies with CSE and OSE specifically defined and discussed as independent variables, and (4) studies that identified at least one cognition-related indicator as a dependent variable. After eliminating duplicate or irrelevant articles, the remaining articles were subjected to a full-text evaluation.…”
Section: Selection Criteriamentioning
confidence: 99%
“…jointly analyzed the selected articles. After excluding articles that did not meet our screening criteria, a total of 19 studies, including 15 cross-sectional studies [4,20,25,[40][41][42][43][44][45][46][47][48][49][50][51] and 4 intervention studies [21,23,24,52] were selected for the analysis. The cross-sectional studies and intervention studies were analyzed separately.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Open-skill exercises are those that require an individual to react in a dynamic way to a changing, unpredictable environment (e.g., badminton, racquetball). 13 Exercises such as walking and running would be considered "closed-skill" exercises as the environment is relatively stable, predictable, and selfpaced. 13 Recent research demonstrates that, at the same given intensity (60% of heart rate reserve, HRR), openskilled acute exercise (30-min bout) was more effective in enhancing BDNF and executive function when compared to closed-skill acute exercise.…”
Section: Introductionmentioning
confidence: 99%
“…13 Exercises such as walking and running would be considered "closed-skill" exercises as the environment is relatively stable, predictable, and selfpaced. 13 Recent research demonstrates that, at the same given intensity (60% of heart rate reserve, HRR), openskilled acute exercise (30-min bout) was more effective in enhancing BDNF and executive function when compared to closed-skill acute exercise. 14 In the current study, we are going to extend this emerging question by examining whether open vs. closed-skilled acute exercise has a differential effect on memory function, which, to date, has TUOMS P R E S S yet to be examined in the literature.…”
Section: Introductionmentioning
confidence: 99%